State sector and divestment in Trinidad and Tobago : some preliminary findings. - SERGEANT, Kelvin (1992)
Traces the growth, financial performance and efforts to dismantle the state sector in Trinidad and Tobago. Expresses the view that too little has taken place and the time span is too short for any proper assessment.